LOW AMPLITUDE RHYTHMIC CONTRACTION FREQUENCY IN HUMAN DETRUSOR STRIPS CORRELATES WITH PHASIC INTRAVESICAL PRESSURE WAVES - Colhoun, Andrew F (World J Urol, 2016)
PURPOSE: Low amplitude rhythmic contractions (LARC) occur in detrusor smooth muscle and may play a role in storage disorders such as overactive bladder (OAB) and detrusor overactivity (DO). The purpose of this study was to determine whether LARC frequencies identified in vitro from strips of human urinary bladder tissue correlate with in vivo LARC frequencies, visualized as phasic intravesical pressure (p(ves)) waves during urodynamics (UD). METHODS: After IRB approval, fresh strips of human urinary bladder were obtained from patients. LARC was recorded with tissue strips at low tension (<2g) and analyzed by fast Fourier transform (FFT) to identify LARC signal frequencies. Blinded UD tracings were retrospectively reviewed for signs of LARC on the p(ves) tracing during filling and were analyzed via FFT. RESULTS: Distinct LARC frequencies were identified in 100% of tissue strips (n=9) obtained with a mean frequency of 1.97±0.47 cycles/min (33±8 mHz). Out of 100 consecutive UD studies reviewed, 35 visually displayed phasic p(ves) waves. In 12/35 (34%), real p(ves) signals were present that were independent of abdominal activity. Average UD LARC frequency was 2.34±0.36 cycles/min (39±6 mHz) which was similar to tissue LARC frequencies (p=0.50). A majority (83%) of the UD cohort with LARC signals also demonstrated detrusor overactivity. CONCLUSIONS: During UD, a subset of patients displayed phasic p(ves) waves with a distinct rhythmic frequency similar to the in vitro LARC frequency quantified in human urinary bladder tissue strips. Further refinements of this technique may help identify subsets of individuals with LARC–mediated storage disorders.